The Role of Teacher Training and Parental Support in Developing Kindergarten Children’s Potential: A Quantitative Study at Korwilcam Kersana Brebes - Yeti Ariyanti; Dewi Apriani; Hanung Sudibyo (FKIP - Universitas Riau, 2026)
The development of children’s potential in early childhood education is influenced by educational and family factors. Research on the simultaneous contribution of teacher training and parental support to kindergarten children’s development remains limited, particularly in schools under Korwilcam Satpendik Kersana, Brebes Regency, indicating a significant research gap. This study aimed to analyze the influence of both variables on children’s potential development. A quantitative survey was employed involving 85 respondents selected through proportional random sampling. Data were collected using validated questionnaires measuring teacher training, parental support, and children’s potential development across cognitive, social, and emotional indicators, with reliability confirmed through Cronbach’s Alpha. Multiple regression analysis was applied. The results showed that teacher training significantly affected children’s potential development (β = 0.421; p = 0.003), while parental support demonstrated a stronger effect (β = 0.467; p = 0.001). Simultaneously, both variables explained 68.4% of the variance (R² = 0.684). These findings confirm that effective teacher training combined with active parental involvement plays a crucial role in optimizing children’s developmental potential, providing empirical evidence for early childhood education policy.